AN INVESTIGATION INTO STUDENTS’ VARIATION OF SPEAKING SCORES WITH DIFFERENT RATERS AND TOPICS A CASE STUDY: SECOND-YEAR ENGLISH-MAJORED STUDENTS AT A LANGUAGE UNIVERSITY = NGHIÊN CỨU VỀ SỰ DAO ĐỘNG ĐIỂM BÀI THI NÓI CỦA HỌC SINH VỚI CÁC CHỦ ĐỀ KHÁC NHAU VÀ NGƯỜI CHẤM KHÁC NHAU: MỘT NGHIÊN CỨU VỀ SINH VIÊN NĂM THỨ HAI CHUYÊN NGÀNH TIẾNG ANH TẠI MỘT TRƯỜNG ĐẠI HỌC ĐÀO TẠO NGOẠI NGỮ - Ngô, Phương Nga (2020)
This study investigated the influence of topics and raters on the speaking scores of 20 sophomores at FELTE, ULIS, VNU, as well as whether or not there exist differences between the two raters in the scoring process. The speaking topics were derived from an English test preparation course that these students are currently studying, and its format was the same as part 3 of the IELTS speaking test. A survey and interviews were utilized to collect the data, which were then analysed by paired-samples T-Test and content-based analysis respectively. The analysis of the result revealed that no significant differences were detected between the two raters’ scores of the candidates. However, the change in topics might influence the scores of the candidates. In addition, interviews with raters indicated that there exist huge differences between the two raters in their rating process, yet surprisingly, these differences did not seem to exert any significant impact on the scores.